(untitled) (Mustansiria Dental Journal, 2018)
To investigate the characteristic intensity and pattern of staining of P53 and Ki67 in oral squamous cell carcinoma in different grading of lesions. Thirty patients with oral squamous cell carcinoma were collected and used to detect the intensity and pattern of staining of P53 and ki67 markers by immunohistochemical method. Immunoreactivity of this study for P53 found that 21 (70%) were positive in different grading of disease. Most frequent combination includes strong intensity in 11 cases (52%) and diffuse pattern in 15 cases (71%). Immunoreactivity of Ki67 in oral squamous cell carcinoma indifferent grading was found positivity for ki67 in 25 cases (83%) and the most frequent pattern of staining was the scattered which seen in 20 cases (80%) and 5 cases (20%) had diffuse pattern of staining. In conclusion the study revealed that the intensity and pattern of staining of P53 and Ki67 correlate with well differentiated oral squamous cell carcinoma.